2020
DOI: 10.1111/1751-7915.13623
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial community and metabolome dynamics and their interactions modulate fermentation process of whole crop corn silage prepared with or without inoculants

Abstract: Summary Multi‐omics approach was adopted to investigate the modulation of bacterial microbiota and metabolome as well as their interactions in whole crop corn ensiling systems by inoculating homofermentative Lactobacillus plantarum or heterofermentative Lactobacillus buchneri. Inoculations of the two different inoculants resulted in substantial differences in microbial community and metabolic composition as well as their dynamics in ensiled corn. Inoculants also altered the correlations of microbiota in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
106
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 61 publications
(66 reference statements)
21
106
6
2
Order By: Relevance
“…These routes lead to lactic acid accumulation during fermentation. Here, the relative abundance of energy metabolism was higher in the control and lower in Pp-and Ef-inoculated silages during the entire ensiling period, which was inconsistent with the report of Xu et al (2020) which energy metabolism was predicted to be upregulated in the inoculated silages in the middle stage of fermentation. The abundance of nucleotide metabolism was higher in the Pp-inoculated silages The relative abundance (%)…”
Section: Functional Shifts Of Bacterial Communities In Alfalfa Silagecontrasting
confidence: 99%
See 2 more Smart Citations
“…These routes lead to lactic acid accumulation during fermentation. Here, the relative abundance of energy metabolism was higher in the control and lower in Pp-and Ef-inoculated silages during the entire ensiling period, which was inconsistent with the report of Xu et al (2020) which energy metabolism was predicted to be upregulated in the inoculated silages in the middle stage of fermentation. The abundance of nucleotide metabolism was higher in the Pp-inoculated silages The relative abundance (%)…”
Section: Functional Shifts Of Bacterial Communities In Alfalfa Silagecontrasting
confidence: 99%
“…2). Our previous study showed that inoculation changed the correlation of bacterial communities, and the identified keystone taxa were completely different among the control, L. plantarum, and L. buchneri-inoculated silages (Xu et al, 2020). Similarly, the present results also indicated that different inoculants and their combinations obviously altered the correlations within microbiota and the keystone species for modulating the fermentation process.…”
Section: Bacterial Communities and Dynamics In Alfalfa Silagesupporting
confidence: 71%
See 1 more Smart Citation
“…In the past decade, the microbial communities during ensiling have become a research focus of silages with the development of next-generation sequencing technologies (Romero et al, 2018). Gharechahi et al (2017), Keshri et al (2018), and Xu et al (2020) reported the dynamics of microbial community during the ensiling of whole-plant corn silages treated with LAB or collected from different locations. Guan et al (2018) determined the bacterial community in corn silages prepared with farm bunker-silo in Southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…The LAB was usually used as silage additives to promote the ensiling process and improve the fermentation quality of end-silages (Weinberg and Muck, 1996). Some recent studies indicated that adding inoculants (containing selected LAB strains) changed the microbial community by making LAB dominated microorganism as soon as possible (Keshri et al, 2018;Guan et al, 2020;Xu et al, 2020). Several authors have reported that LAB prepared from alfalfa is more effective in improving the fermentation quality of alfalfa silage than that from other forage sources (Ohshima et al, 1997;Wang et al, 2009;Denek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%